2008
DOI: 10.4103/0250-474x.44603
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric method for determination of duloxetine hydrochloride in bulk and pharmaceutical dosage forms

Abstract: A simple accurate, sensitive and reproducible spectrofluorimetric method was developed for the analysis of duloxetine hydrochloride in pure and pharmaceutical dosage form. Duloxetine hydrochloride showed strong native fluorescence in 0.05 M acetic acid having excitation at 225 nm and emission at 340 nm. Effect of different solvents were thoroughly investigated. The calibration graph was linear in the range from 0.020 to 0.400 μg/ml. The proposed method was statistically validated and successfully applied for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…A survey of literature showed few analytical methods has been reported for determination of duloxetine hydrochloride in human serum and biological fluids using tandem MS and LC-MS methods 3 and HPLC 4-5 method for the estimation of duloxetine hydrochloride in pharmaceutical preparations. Determination of duloxetine hydrochloride by spectroflourimetric method [6][7] has also been reported. To the best of our knowledge, there is no report on UV-Visible spectrophotometric method for its estimation.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of literature showed few analytical methods has been reported for determination of duloxetine hydrochloride in human serum and biological fluids using tandem MS and LC-MS methods 3 and HPLC 4-5 method for the estimation of duloxetine hydrochloride in pharmaceutical preparations. Determination of duloxetine hydrochloride by spectroflourimetric method [6][7] has also been reported. To the best of our knowledge, there is no report on UV-Visible spectrophotometric method for its estimation.…”
Section: Introductionmentioning
confidence: 99%
“… Pure samples: Galantamine hydrobromide was kindly supplied by Cadila Pharmaceutical Ltd. (Ahmedabad, India) Market samples: Galamer 4 mg tablets (Sun Pharmaceutical ltd.) Chemical and Reagents: Distilled water prepared by distillation unit in the laboratory was used throughout the study. [ 8 9 10 11 12 13 ] …”
Section: Methodsmentioning
confidence: 99%
“…Though determination of duloxetine hydrochloride by spectrofluorimetric method [9,10] has been reported but there is no UV-visible spectrophotometric method for determination of duloxetine, which motivates us to develop and carry out this research work. This present research paper was found to be simple, precise, and accurate and validated as per ICH guidelines and rapid for the estimation of duloxetine in pure form.…”
Section: Introductionmentioning
confidence: 99%